Invited review: Intergovernmental Panel on Climate Change, agriculture, and food—A case of shifting cultivation and history. (13th June 2019) - Porter, John R.; Challinor, Andrew J.; Henriksen, Christian Bugge; Howden, Stuart Mark; Martre, Pierre; Smith, Pete
Abstract: Since 1990, the Intergovernmental Panel on Climate Change (IPCC) has produced five Assessment Reports (ARs), in which agriculture as the production of food for humans via crops and livestock have featured in one form or another. A constructed database of the ca. 2, 100 cited experiments and simulations in the five ARs was analyzed with respect to impacts on yields via crop type, region, and whether adaptation was included. Quantitative data on impacts and adaptation in livestock farming have been extremely scarce in the ARs. The main conclusions from impact and adaptation are that crop yields will decline, but that responses have large statistical variation. Mitigation assessments in the ARs have used both bottom‐up and top‐down methods but need better to link emissions and their mitigation with food production and security. Relevant policy options have become broader in later ARs and included more of the social and nonproduction aspects of food security. Our overall conclusion is that agriculture and food security, which are two of the most central, critical, and imminent issues in climate change, have been dealt with an unfocussed and inconsistent manner between the IPCC five ARs. This is partly a result of not only agriculture spanning two IPCC working groups but also the very strong focus on projections from computer crop simulation modeling. For the future, we suggest a need to examine interactions between themes such as crop resource use efficiencies and to include all production and nonproduction aspects of food security in future roles for integrated assessment models. Abstract : Since 1990, the IPCC has produced five Assessment Reports (ARs) including agriculture. Using a database of the ca. 2, 100 cited experiments and simulations in the five ARs, our conclusions are that crop yields decline but with large statistical variation. Livestock effects have almost been quantitatively absent. Mitigation assessments need better to link emissions and their mitigation with food production and security; agriculture has been dealt with inconsistently between the IPCC five ARs. IPCC needs to examine interactions between crop resource use efficiencies and include production and nonproduction aspects of food security. See commentary on: https://onlinelibrary.wiley.com/doi/10.1111/gcb.15022